2001
DOI: 10.1051/0004-6361:20010889
|View full text |Cite
|
Sign up to set email alerts
|

Multi-colour light variation of AGB stars observed with ISO

Abstract: Abstract. New visual light curves and infrared multi-epoch photometry are presented for a sample of AGBstars spectroscopically observed with ISO. While the ISO work is or will be presented elsewhere, the aim of this paper is to give an overview of the properties of the light change of the objects. This information is crucial for the interpretation of the valuable ISO material. Using the University of Vienna Twin Automatic Photoelectric Telescope (APT) we monitored the stars of our sample in the photometric ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 22 publications
(26 reference statements)
8
54
1
Order By: Relevance
“…Thus, only some indications can be listed here. Kerschbaum et al (2001;their Fig. 5) found that their lightcurve in the K-filter of the C-rich Mira T Dra lags behind the visual data (AAVSO) by 0.06 in phase.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, only some indications can be listed here. Kerschbaum et al (2001;their Fig. 5) found that their lightcurve in the K-filter of the C-rich Mira T Dra lags behind the visual data (AAVSO) by 0.06 in phase.…”
Section: Discussionmentioning
confidence: 92%
“…Percy & Fleming 1992) for which Hipparcos found variations with an amplitude of 0.1 mag and a period of only 6.3 days (Koen & Eyer 2002). However, more recently, samples of these Hipparcos short-period SRs have been the subject of other dedicated photometric surveys, such as those performed by and Kerschbaum et al (2001), which could not confirm the presence of any variability with a period below 35 days in any of their targets. Kerschbaum et al (2001) suggest some instrumental artefact of Hipparcos.…”
Section: The Calibrator Star: Hr 5512mentioning
confidence: 96%
“…However, more recently, samples of these Hipparcos short-period SRs have been the subject of other dedicated photometric surveys, such as those performed by and Kerschbaum et al (2001), which could not confirm the presence of any variability with a period below 35 days in any of their targets. Kerschbaum et al (2001) suggest some instrumental artefact of Hipparcos. We are therefore confident that the brightness of our calibrator HR 5512 has not changed significantly during the observing run.…”
Section: The Calibrator Star: Hr 5512mentioning
confidence: 99%
“…They are also important for stellar and galactic evolution, especially in connection with the formation of planetary nebulae. For reviews on AGB envelopes and their properties see, e.g., Habing & Olofsson (2004) and Kerschbaum et al (2011).…”
Section: Introductionmentioning
confidence: 99%